The Missionary Home as a Site for Mission: Perspectives from Belgian Congo - Maxwell, David (Studies in church history, 2014)
Nineteenth- and twentieth-century Protestant missionaries considered themselves exemplars of the Christian home. They devoted considerable energy to writing about domesticity and to constructing model homes in the mission field. In spite of their good intentions there was often a large gap between their ideals and the realities of life on mission stations. By means of a case study of a Pentecostal faith mission in Katanga, Belgian Congo, this essay demonstrates how models of the Western Christian home were unsustainable and examines the manner in which missionaries coped with unfulfilled domestic dreams. It shows how Western notions of the Christian home were undermined by the harshness of the tropical environment, the disparity in numbers between male and female missionary vocations, and the persistence of African notions of domesticity. The missionaries endured the material and emotional deprivations of life in the bush through faith in a providential God and by constructing intimate but tense relationships with African Christians. The essay begins with a discussion of some of the most pertinent scholarship on missionaries and domesticity.